Cardiovascular and metabolic responses during indoor climbing and laboratory cycling exercise in advanced and élite climbers - Limonta, E.; Brighenti, A.; Rampichini, S.; Cè, E.; Schena, F.; Esposito, F. (European Journal of Applied Physiology, 2018)
Purpose: To validate heart rate (fH) as an effective indicator of the aerobic demands of climbing, the fH vs oxygen uptake (VO2) relationship determined during cycling exercise and climbing on a circular climbing treadwall was compared. Possible differences in maximum aerobic characteristics between advanced and élite climbers were also assessed. Methods: Seven advanced and six élite climbers performed a discontinuous incremental test on a cycle ergometer and a similar test on a climbing treadwall. Cardiorespiratory and gas exchange parameters were collected at rest and during exercise. Results: The fH vs VO2 relationship was steeper during cycling than climbing at submaximal exercise for both groups and during climbing in the élite climbers as compared to the advanced. At peak exercise, VO2 was similar during both cycling and climbing (3332 ± 115 and 3193 ± 129 ml/min, respectively). Despite similar VO2peak, the élite climbers had a higher peak workload during climbing (11.8 ± 0.8 vs 9.2 ± 0.3 m/min in élite and advanced climbers, respectively; P = .024) but not during cycling (291 ± 13 and 270 ± 12 W in élite and advanced climbers, respectively). Conclusions: Our findings indicate that care should be taken when energy expenditure during climbing is estimated from the fH vs VO2 relationship determined in the laboratory. The level of climbing experience significantly affects the energy cost of exercise. Last, the similar aerobic demands of cycling and climbing at peak exercise, suggest that maximum VO2 may play an important role in climbing performance. Specific training methodologies should be implemented to improve aerobic power in climbers.